Sustainable tandem acylation/Diels–Alder reaction toward versatile tricyclic epoxyisoindole-7-carboxylic acids in renewable green solvents - Yıldırım, Ayhan (Beilstein Journal of Organic Chemistry, 2024)
Tandem Diels–Alder reactions are often used for the straightforward formation of complex natural compounds and the fused polycyclic systems contained in their precursors. In the second step of this reaction, regio- and stereochemically controlled intramolecular cyclization leads to the formation of versatile nitrogen-containing tricyclic systems. However, these useful organic transformations are usually carried out in highly toxic organic solvents such as benzene, toluene, chloroform, etc. Despite recent efforts by 'green chemists', synthetic chemists still use these traditional toxic organic solvents in many of their reactions, even though safer alternatives are available. However, in addition to the harmful effects of these petrochemical solvents on the environment, the prediction that their resources will run out in the near future has led 'green chemists' to explore solvents that can be derived from renewable resources and used effectively in various organic transformations. In this context, we have shown for the first time that the 100% atom-economical tandem Diels–Alder reaction between aminofuranes and maleic anhydride can be carried out successfully in vegetable oils and waxes. The reaction was successfully carried out in sunflower seed oil, olive oil, oleic acid and lauryl myristate under mild reaction conditions. A series of epoxyisoindole-7-carboxylic acid and bisepoxyisoindole-7-carboxylic acids were obtained in good yields after a practical isolation procedure. The results obtained in this study demonstrate the potential of vegetable oils and their renewable materials to provide a reaction medium that is more sustainable than conventional organic solvents in cascade Diels–Alder reactions and can be used repeatedly without significant degradation. These materials also allow the reaction to be completed in less time, with less energy consumption and higher yields.
Keywords: biobased solvent; epoxyisoindoles; furanics; green chemistry; intramolecular Diels–Alder reaction